Constructions and properties of zinc coordination polymers based on 3, 5-di(4H-1, 2, 4-triazol-4-yl) benzoic acid with different polycarboxylic acids as a secondary ligand. (9th March 2017) - Jiang, Wen-Hong; Liu, Ji-Long; Niu, Li-Zhong; Liu, Bin; Yu, Ying-Hui; Hou, Guang-Feng; Ma, Dong-Sheng
Graphical abstract: Five zinc coordination polymers1 –5 were constructed based on the bifunctional ligand 3, 5-di(4H-1, 2, 4-triazol-4-yl)benzoic acid (HL) with three aromatic multicarboxylic acids, 1, 4-benzenedicarboxylic acid (H2 p -BDC), 1, 3, 5-benzenetricarboxylic acid (1, 3, 5-H3 BTC) and 1, 2, 4, 5-benzenetetracarboxylic acid (H4 BTEC), adopted as secondary ligands. It was also found that the fluorescence of1 –5 could be quenched by nitrobenzene (NB), indicating their potential application as sensory materials. Abstract: Five zinc coordination polymers, namely [Zn(L)(NO3 )]·(H2 O) n (1 ), Zn2 (L)2 ( p -BDC) n (2 ), [Zn2 (H2 O)2 (L)(1, 3, 5-BTC)]·H2 O n (3 ), [Zn2 (L)2 (H2 BTEC)]·2H2 O n (4 ) and [Zn3 (H2 O)4 (L)2 (BTEC)]·6(H2 O) n (5 ), HL = 3, 5-di(4H-1, 2, 4-triazol-4-yl)benzoic acid, H2 p -BDC = 1, 4-benzenedicarboxylic, 1, 3, 5-H3 BTC = 1, 3, 5-benzenetricarboxylic acid, H4 BTEC = 1, 2, 4, 5-benzenetetracarboxylic acid, were synthesized under solvothermal conditions. Single-crystal X-ray analyses show that complex1 exhibits two-dimensional (2D) double-layered 3, 4L88 nets with π–π interactions. Complexes2, 3 and4 display the same 2D topological structures as that of complex1, except for the further formation of different 2D → 3D supramolecular structures in2 and4 . Complex2, with a deprotonated [ p- BDA] 2− ligand, forms interpenetrated structures with the (6 2 ·8 4 )(6 6 )4 topology built by π–π interactions, whereas complex4, built by partially deprotonated [H2 BTEC] 2− ligands, forms a similar interpenetrated three-dimensional (3D) framework with a point symbol of (6 6 ). When the mixed ligand was changed into 1, 3, 5-H3 BTC in3, the coordination mode of one Zn(II) atom is trigonal–bipyramidal as opposed to tetrahedral in1, 2 and4, and each [L] − anion acts as a tetradentate ligand linking four Zn(II) ions instead of a tridentate ligand, generating a 3, 4, 4, 5-connected (6 3 )(6 6 )2 (6 9 ·8) framework in3 . In complex5, the completely deprotonated H4 BTEC ligand connects four Zn(II) ions as a tetracarboxylate ligand to produce a 2-fold interpenetrated three-dimensional (3D) framework with a point symbol of (4·6·7 2 ·8 2 )2 (4 2 ·7 2 ·8 2 )(6 2 ·7 3 ·8)2 . The five complexes have also been characterized by elemental analysis, infrared spectroscopy, powder X-ray diffraction and thermogravimetry measurements. It was also found that the fluorescence of complexes1 –5 could be quenched by nitrobenzene (NB), indicating their potential application as sensory materials.